Estimation of stature based on anthropometry of percutaneous length of arm among males of Central India Region - Pateria, Devesh; Thakur, P S; Singh, B K; Tomar, J S; Shrivastava, Mohit (Journal of Indian Academy of Forensic Medicine, 2021)
Identification means determination of exact individuality of a person. It is one of the important criteria for conducting autopsy, apart from finding the cause and time since death. Stature is an important parameter to establish identity of an unknown corpse. It is being used by medico legal experts when either complete or parts of human body are recovered. Establishing the identity of an individual from mutilated, decomposed and amputated body fragments has become an important necessity in recent times due to natural disasters like earthquakes, tsunamis, cyclones, floods and man-made disasters like terror attacks, bomb-blasts, mass accidents, wars, and plane crashes etc. Hence the present study has been undertaken and is aimed at and concentrated on finding the co-relation between supine length and anthropometric measurements of both sides (right and left) arm of male in central India population belonging to age group 21 to 60 years in mortuary of Forensic Medicine Department, M.G.M. Medical College and M.Y. Hospital, Indore (M.P.). The mean percutaneous arm length on right side and left (32.53±1.527) and (32.56±1.565), cm respectively, whereas the mean stature was found to be 165.64 ± 5.038 cm. In this study maximum stature in males was found to be 180.2 cm and minimum stature was found to be 152.0 cm. Percutaneous arm length and stature was found to be positively correlated and association was highly significant. The multiplication factor for percutaneous arm length was found to be 5.09. .